2022
DOI: 10.3390/ijms23158831
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of miRNAs and Their Predicted Target Genes Indicates That Gene Expression in Atlantic Salmon Gill Is Post-Transcriptionally Regulated by miRNAs in the Parr-Smolt Transformation and Adaptation to Sea Water

Abstract: Smoltification (parr-smolt transformation) is a complex developmental process consisting of developmental changes that lead to remodeling of the Atlantic salmon gill. Here, the expression changes of miRNAs and mRNAs were studied by small-RNA sequencing and microarray analysis, respectively, to identify miRNAs and their predicted targets associated with smoltification and subsequent sea water adaptation (SWA). In total, 18 guide miRNAs were identified as differentially expressed (gDE miRNAs). Hierarchical clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Changes in the immune response of the miR-30 family during environmental stress and development have been recorded. Alice et al proposed that the miRNA-30 family is an important post-transcriptional regulator of parr-smolt transformation and seawater adaptation, and their enrichment analysis of target mRNAs showed that several biological processes are associated with the immune system [47]. In this work, it was speculated that miR-30b-5p's high expression had a regulatory function in the silver carp's antibacterial response.…”
Section: Discussionmentioning
confidence: 81%
“…Changes in the immune response of the miR-30 family during environmental stress and development have been recorded. Alice et al proposed that the miRNA-30 family is an important post-transcriptional regulator of parr-smolt transformation and seawater adaptation, and their enrichment analysis of target mRNAs showed that several biological processes are associated with the immune system [47]. In this work, it was speculated that miR-30b-5p's high expression had a regulatory function in the silver carp's antibacterial response.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, seven genes involved in transmembrane transporter activity ( slc4a1b , slc39a10 , slc15a4 , slc20a1a , slc25a25b , slc45a2 , and slc16a5a ) and three genes involved in calcium homeostasis ( cabp1 , camk2a , and cacna1bb ) were also described. Genome epigenetic modifications and non-coding RNAs play a significant role in the rapid adaptation to changes in the salinity of the environment in fish [ 15 , 54 , 55 , 56 , 57 ]. Table S2 represents several such genes, including piwil1 ( piwi-like1 RNA-mediated gene ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that the miR-30 family can regulate oxidative stress, apoptosis, autophagy, inflammation, and tumor progression in mammals [ 23 , 24 , 25 ]. With the development of the research, the changes in the miR-30 family’s immune response during environmental stress and the development of teleost fish have been reported [ 26 ]. Additionally, miR-30b-5p plays a broad regulatory role in Gram-negative bacterial infections in silver carp according to our earlier studies [ 27 ].…”
Section: Discussionmentioning
confidence: 99%